OPTIMIZING THE TAX RISK OF PROFIT TAX THROUGH TAX CONTROL (World Bulletin of Social Sciences, 2025)
This article is devoted to the analysis of the issues of optimizing tax risk for profit tax through tax control.
Keywords: Tax risk; tax control; tax risks